Factors Affecting Overseas Employment of Female Workers from Bangladesh - Nessa, Hazera-Tun; Moniruzzam, Md.; Hossain, Md. Sazzad; Wadood, Sayed Naimul (International Journal of Economics and Financial Issues, 2021)
This study attempts to explore the impacts of some demographic, economic and cultural factor's effects on overseas employment of female workers as well as on overseas employment of total workers from Bangladesh. The Gravity model of trade is applied here with the panel data of 12 countries and 22 years. The random effect analysis is applied since some variables which are time-invariant and important for the study. The main gravity variables – Gross Domestic Product (GDP), population and distance- are found to be well fitted with literatures with expected signs and level of significance. The magnitude of impacts differs for female overseas workers than total overseas workers. The study reveals that while the effect of religion is insignificant in case of total overseas employment its impact on female overseas employment is highly significant. The negative effects of language variables for both types of employments reflect the fact that most of the workers specially women workers migrated to abroad as home maid and didn't get the training on official language of Bangladesh, English. Furthermore, the opportunity of earnings at destination countries proxied by remittances flows from those countries to Bangladesh has highly positive impact and the magnitude is higher for female overseas workers. The study suggests policies and required support services should be provided to mitigate the migration cost. Also, countries with higher GDP, similar religion and higher income, networking and employment opportunities should be chosen as potential new labour market for the female workers of Bangladesh. Keywords: Female worker's overseas Employment, Gravity Model, Panel Data, Random Effect Analysis, Bangladesh JEL Classifications: E24, C130 DOI: https://doi.org/10.32479/ijefi.11626